Circadian preference and trait impulsivity, sensation-seeking and response inhibition in healthy young adults. (March 2015) - Kang, Jee In; Park, Chun Il; Sohn, Sung-yun; Kim, Hae Won; Namkoong, Kee; Kim, Se Joo
Abstract : Circadian preference has been considered related with impulsivity. The purpose of the present study was to evaluate the relationship between circadian typology and impulsivity measured by the Barratt Impulsivity Scale (BIS), sensation-seeking measured by the Sensation Seeking Scale - Form V (SSS-V) and response inhibition elicited by the GO/NO-GO paradigm. A total of 503 Korean healthy college students (288 males and 215 females) completed the Composite Scale of Morningness (CSM) for circadian typology and the BIS and SSS-V for impulsivity and risk taking, respectively. A subset of 142 subjects additionally performed the computerized GO/NO-GO task for motor response inhibition. A significant association was found between the circadian typology of the CSM and impulsivity of the BIS and disinhibition of SSS-V. In addition, there was a difference in trend level between the circadian typology and response inhibition elicited by the GO/NO-GO test. Regarding circadian preference, evening types were significantly associated with higher impulsivity on the BIS, disinhibition on the SSS-V and lower rate of successful inhibition on the GO/NO-GO task compared to morning types. The present results showed significant relationships between circadian preference and impulsivity and sensation-seeking personality traits. In particular, our findings suggest that high impulsivity, disinhibition and impaired response inhibition are more related to evening types. Circadian preference might be associated with psychiatric problems interacting with some aspects of personality traits such as inhibitory control.